The Concept of Grand Strategy and the Specific Case of the Russian State: Array - Blidaru, Sebastian (Acta Universitatis Danubius. Relationes Internationales, 2020)
When talking about International Relations, for the last decades, the popularity of the concept of grand strategy has continuously increased. This led to the present situation when we have a disputed term with multiple distinct definitions. In this context, the central objective of this paper is to select and evaluate the existing analyses of the grand strategy of the Kremlin between 2000 and 2019. Another important goal is to clarify the main elements of this concept. To identify the relevant literature, we used a series of academic journals such as Cambridge Journals, ProQuest Central, Sage Journals and others. The present analysis shows that one category of authors argue that the grand strategy of the Russian Federation has become more assertive. According to their opinion, the Moscow administration is willing to use all means available in order to achieve the main objectives: the status of great power; the return to the spheres of influence; and the return to a multipolar international system. A second category explores sub-elements of grand strategy such as the importance of Ukraine, or the impact of the war in Georgia. Finally, one researcher argues that Russia does not have a grand strategy at all. In conclusion, this paper shows that many elements remain to be explored in relation to a topic of such complexity as the grand strategy of the Russian Federation.